Neuron-specific biomarkers predict hypo- and hyperalgesia in individuals with diabetic peripheral neuropathy - Morgenstern, Jakob; Gröner, Jan; Jende, Johann; Kurz, Felix T.; Strom, Alexander; Göpfert, Jens Christian; Kender, Zoltán; Le Marois, Maxime; Brune, Maik; Kuner, Rohini; Herzig, Stephan; Roden, Michael; et al. (Diabetologia, 2021)
The individual risk of progression of diabetic peripheral neuropathy is difficult to predict for each individual. Mutations in proteins that are responsible for the process of myelination are known to cause neurodegeneration and display alteration in experimental models of diabetic neuropathy. In a prospective observational human pilot study, we investigated myelin-specific circulating mRNA targets, which have been identified in vitro, for their capacity in the diagnosis and prediction of diabetic neuropathy. The most promising candidate was tested against the recently established biomarker of neural damage, neurofilament light chain protein.
Gesehen am 28.07.2023